Clinical Heinz Body Anemia in a Cat After Repeat Propofol Administration Case Report - Baetge, Courtney L.; Smith, Lauren C.; Azevedo, Carolina P. (Frontiers in Veterinary Science, 2020)
Heinz body formation has been reported in cats repeatedly administered propofol for anesthesia induction, although the resultant changes were deemed of little clinical significance1,2. This report suggests repeated propofol administration to some individual cats might induce anemia with clinical signs and cessation of propofol administration may result in rapid resolution. A 9-year-old American Domestic Shorthair cat receiving a 20-fraction radiation protocol for lateral thoracic fibrosarcoma showed lethargy, decreased appetite and activity, and Heinz body (3+ on blood smear examination) anemia (packed cell volume 22%; reference interval 24-45%) after 12 repeated propofol anesthesia inductions. The anesthesia induction protocol was adjusted to exclude propofol. Over the following week, the anemia resolved (packed cell volume, 30%), and the cat’s activity level, appetite and attitude improved. The total dose of propofol received over the 12 treatments was 62.4 mg/kg.